Peningkatan Kadar Hemoglobin Remaja Putri dengan Pemberian Kukis Pelangi Ikan Gaguk (Arius thalassinus) - Dwi Putri Cahyati; Betty Yosephin Simanjuntak; Ahmad Rizal (Politeknik Kesehatan Tanjung Karang, 2020)
Women have a higher risk of anemia, especially in young women. This study aimed to determine the effect of giving the rainbow fish cookies (Arius thalassinus) to changes in hemoglobin levels in young girls in Pancasila MTs Bengkulu City. This study was a pre-experimental design study with one group pretest and posttest design. The sampling technique was done by purposive sampling as many as 37 people. The treatment given is in the form of 10 pieces (100gr) rainbow fish cookies for 30 days to young women. This research was carried out by checking the levels of hemoglobin before and after the administration of the rainbow fish cookies. The analysis used is the dependent parametric T-test. The average recall of young women 3x24 hours was Fe intake by 5,40mg, protein intake by 40,4 grams, and vitamin C intake by 5,7mg. In the provision of cookies rainbow fish (Arius thalassinus) obtained an average value of hemoglobin levels before that is 10,70g/dL and after being given treatment to 12,87g/dL with a p-value of 0,000 (<0,05). There is an effect of giving cookies rainbow fish to hemoglobin levels in young girls in Pancasila MTs Bengkulu City.